A CAD-based approach for measuring volumetric error in layered manufacturing. (July 2017) - Panda, Biranchi Narayan; Bahubalendruni, Raju MVA; Biswal, Bibhuti Bhusan; Leite, Marco
Rapid prototyping uses layered manufacturing technology to produce functional parts directly from 3D computer-aided design model without involving any tools and human intervention. Due to layer by layer deposition, volumetric error remains in the part which is basically the volumetric difference between computer-aided design model and the fabricated part. This volumetric error causes poor dimensional accuracy and surface finish, which has limited the widespread applications of rapid prototyping. Although rapid prototyping is able to produce functional parts in less build time with less material wastage, today many industries are looking for better surface quality associated with these parts. Literature discloses that the part quality can be improved by selecting proper build orientation that corresponds to minimum volumetric error. In support of this, current study presents a computer-aided design-based novel methodology to precisely measure the volumetric error in layered manufacturing process, in particular fused deposition modeling process. The proposed method accepts computer-aided design model of the part in .CAT format and automatically calculates volumetric error for different build orientations. An Excel function is integrated with it to determine optimum build orientation based on minimum volumetric error. Several simple and complex examples verified the robustness of our proposed methodology. We anticipate that the current invention will help future rapid prototyping users in producing high-quality products through an intelligent process planning.